House buyer perceptions on the value of water and grey water recycling systems - Horton, David (Cranfield University, 2009)
The population of the East of England is set to increase and climate change predictions suggest that the region will become drier; water resources will therefore come under increasing pressure. In order to meet future water demand and deliver a reliable supply in the years to come, Cambridge Water is assessing the feasibility of installing grey water recycling systems in future housing developments. Grey water is wastewater from showers, baths, and wash basins. Recycling this water is an innovative way to conserve water. Treated grey water is used principally for toilet flushing- which represents about a third of water use in a typical UK household- but also for watering gardens and washing cars. This study investigated house buyer perceptions on the value of water and grey water recycling systems. For this purpose 2000 customers were surveyed using a questionnaire. The aim was to inform Cambridge Water as a water supplier of how receptive their customers would be to receiving a secondary supply of treated grey water for non-potable use. All those sampled had moved into a newly built home in the past two years. Since investing in grey water recycling systems would have little or no financial benefit for the homeowner, the study focused on other potential benefits. The response rate for the survey was 22 per cent and the quantitative data was analysed using descriptive statistics. The results show that there was widespread support for the domestic use of grey water. The overwhelming majority of respondents would be willing to invest in grey water recycling systems because they are concerned about the environment, and to ensure a reliable supply at times of water scarcity. Many of those that objected stated that they would need further information before giving their consent.
Keywords: climate change; Cambridge Water; grey water recycling systems; water scarcity; newly built home; housing developments